2011
DOI: 10.1371/journal.pone.0018779
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immune Responses Both Contribute to Pathological CD4 T Cell Activation in HIV-1 Infected Ugandans

Abstract: HIV-1 disease progression is associated with persistent immune activation. However, the nature of this association is incompletely understood. Here, we investigated immune activation in the CD4 T cell compartment of chronically HIV-1 infected individuals from Rakai, Uganda. Levels of CD4 T cell activation, assessed as co-expression of PD-1, CD38 and HLA-DR, correlated directly to viral load and inversely to CD4 count. Deeper characterization of these cells indicated an effector memory phenotype with relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…These findings are in agreement with previous studies that demonstrated that the CD8 + T cell upregulation of PD-1 occurs in the presence of HLA-DR and CD38 (13). Later, the triple combination of CD38, HLA-DR, and PD-1 was found to correlate strongly with the CD4 count and VL (34). Many of the other individual immunological markers (e.g., CD45RO) also correlated significantly with the various laboratory parameters, but + T cells at baseline (median 5 wk before ART supplementation).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with previous studies that demonstrated that the CD8 + T cell upregulation of PD-1 occurs in the presence of HLA-DR and CD38 (13). Later, the triple combination of CD38, HLA-DR, and PD-1 was found to correlate strongly with the CD4 count and VL (34). Many of the other individual immunological markers (e.g., CD45RO) also correlated significantly with the various laboratory parameters, but + T cells at baseline (median 5 wk before ART supplementation).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, weak CD4þ and CD8þ proliferative responses in HEV viremic subjects could be restored in part in vitro by blocking the PD-1 or CTLA-4 pathways. High levels of PD-1 expression on both CD4þ and CD8þ T-cells have been reported in different chronic viral infections in mice 38 and humans including HIV, 39,40 HBV, 41,42 and HCV. [43][44][45] Some studies found that blocking the PD-1 pathway can restore in part the function not only of CD8þ but also of CD4þ T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…High-level expression of markers of immune activation has been shown to correlate with clinical measures of progressive infection (40,63,88). Recently, it was demonstrated that the coexpression of activation marker CD38 and the inhibitory molecule PD-1 on T cells is highly enriched in HIV-specific CD8 T cells of progressors compared to controllers and closely correlates with viral load and CD4 ϩ T cell loss (25,97). PD-1 expression in HIV-infected subjects has also been linked to persistent viral replica- ) and RMNC (open symbols) of noncontrollers (triangles), controllers (circles), and seronegative subjects (squares) were analyzed using the gating strategies described above.…”
Section: Cd4mentioning
confidence: 99%
“…on April 30, 2019 by guest http://jvi.asm.org/ tion as well as CD4 ϩ T cell activation (25,76). In our patient cohort, the frequency of activated CD4 ϩ and CD8 ϩ PD-1 ϩ CD38 ϩ cells was very significantly increased in rectal mucosae of noncontrollers compared to controllers (P ϭ 0.002 and P ϭ 0.001) or seronegative subjects (P ϭ 0.0002 and P ϭ 0.0002) (Fig.…”
Section: Vol 85 2011 Treg In Rectal Mucosae Of Hiv Noncontrollers 1mentioning
confidence: 99%